Redefining ourselves: A Bosadi (Womanhood) approach - Masenya, Madipoane (Old Testament essays, 1997)
In the light of the past South African history in which Africans were defined, a history in which their identity was defined for them, there is a need for Africans, particularly African women, to re-define themselves. The preceding argument coupled with the lack of scholarly Biblical interpretation aiming at the liberation of African women in South Africa, has prompted the author of this article to propose a Bosadi (Womanhood) approach to the reading of the Bible. An approach which is committed amongst others, to the African-ness of an African-South African woman. This paper gives an elaboration on this approach.